Nurse Responsiveness and Empathy as Predictors of Patient Loyalty: A Cross-Sectional Study in Hospital Care Settings - Widayati, Dhina; Rachmania, Diana (Fundamental and Management Nursing Journal, 2025)
Introduction: Patient loyalty serves as an important indicator in evaluating the overall quality of nursing services within hospital settings. Loyalty reflects a crucial determinant of hospital competitiveness and sustainability. This study aims to analyze the relationship between nurse responsiveness, empathy, and patient loyalty in the hospital service environment. Method: This quantitative cross-sectional study involved 62 patients as respondents using accidental sampling techniques. Patient in the ward patients admitted to the ward during January. Data were collected through questionnaires to measure nurses' responsiveness and empathy through patient perceptions, as well as the Patient Loyalty Questionnaire (PLQ), which includes dimensions of attitudinal loyalty, behavioral loyalty, word of mouth, and recommendation intentions. Data were analyzed using Spearman correlation and Ordinal Logistic Regression. Results: Patient perceptions of nurse responsiveness showed that more than half (66.1%) were in the good category. Similarly, patient perceptions of nurse empathy showed that more than half (71%) were in the good category. Some patients (54.9%) had high loyalty. Analysis of the relationship between responsiveness and loyalty (p=0.001 and r=0.69) and between empathy and loyalty (p=0.001 and r=0.59). Both results indicate that responsiveness and empathy are related to loyalty with the strength of the relationship in the strong category Conclusions: Nurses' responsiveness and empathy are important factors influencing patient loyalty. Hospital management needs to develop training programs to strengthen nurses' skills in responding to patient needs quickly and effectively, as well as work systems that support nurses' quick, responsive, and timely responses in interacting with patients, so that patients feel satisfied and become loyal.